Sistema Web para el manejo de información socioeconómica y de vivienda en las personas afectadas por eventos catastróficos del Ministerio de Inclusión Económica y Social de la Ciudad de Babahoyo - Avilez Vera, Glenda Catiusca (2018)
The computer systems to pass of the time have gone growing at present and one of the main reasons has been the need to be able to conserve and to carry information, in such a way that this one realizes a function with agility, security and efficiency. Computer programs are created and developed through functional tools that provide a fast and easy to use interaction for the realization of the activities of a company in the labor and competitive development helping to obtain a better quality of service for its users. and customers. Currently, many companies to streamline their administrative processes, are in need of using measures to improve their flow of information, which needs to be updated, stored and make efficient use of it on a daily basis, anywhere and any time. The Ministry of Economic and Social Inclusion is responsible for providing assistance to people affected by natural disasters, as well as being responsible for manifesting the respective results to the authorities of the affected population, as well as promoting information security based on to a backup. But the delivery of such information is inappropriate and late becoming a disadvantage for the execution of their activities. Taking into account the inconveniences that are generated when carrying out the functions of the Ministry of Economic and Social Inclusion in cases of disasters, the present technological proposal arises that is oriented to a Web Application for the management of technical information, with the objective to systematize the processes, compensating in this way the needs of this institution.